1983
DOI: 10.2466/pms.1983.56.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Content of Dreams Recalled by Elderly Women

Abstract: At the end of 6 wk., 37 elderly women turned in 145 dream narratives and accompanying emotions. Approximately two emotions were used to describe each dream; enjoyment, surprise, distress, confusion, interest, and fear accounted for 86% of all dream emotions. The emotions of disgust, anger, shame, and contempt were infrequently reported by these elderly persons. The dreams associated with the retirement life style of the elderly exhibited pleasant as well as unpleasant emotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
(3 reference statements)
0
12
1
Order By: Relevance
“…He found that any differences were small and that the dream reports in general were not as emotional or unpleasant as dreams are often claimed to be. In similar fashion, Howe and Blick (1983) had women rate their dream reports on several emotionality dimensions, finding that the emotions in the dreams of older women were rated as more benign.…”
Section: Rating ~Cales For Dream Contentmentioning
confidence: 87%
“…He found that any differences were small and that the dream reports in general were not as emotional or unpleasant as dreams are often claimed to be. In similar fashion, Howe and Blick (1983) had women rate their dream reports on several emotionality dimensions, finding that the emotions in the dreams of older women were rated as more benign.…”
Section: Rating ~Cales For Dream Contentmentioning
confidence: 87%
“…This clearly shows that the external rating method potentially underestimates positive affects. In the same vein, the studies which used the external rating method (e.g., McCarley & Hobson, 1979;Kramer & Brik, 2002) found far lower frequencies of affects in dream reports than the studies which asked subjects explicitly to rate the affects in their dreams (e.g., Foulkes, Sullivan, Kerr, & Brown, 1988;Howe & Blick, 1983;Stairs & Blick, 1979;Strauch & Meier, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, studies that have compared external ratings of emotions to participants’ self-ratings of emotions find that external raters overestimate negative emotions in dreams compared to what the dreamers themselves perceive in the dreams ( Schredl and Doll, 1998 ; Sikka et al, 2014 ), indicating that it is the method that produces the negativity bias. In other studies, the top self-reported emotion has been some form of joy, elation, or excitement ( Howe and Blick, 1983 ; Fosse et al, 2001 ).…”
Section: Arguments For and Against Emotion-processing Theoriesmentioning
confidence: 92%